2017
DOI: 10.3747/co.24.3355
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Treatment Selection and Survival in Advanced Lung Cancer

Abstract: Purpose Despite numerous breakthrough therapies, inoperable lung cancer still places a heavy burden on patients who might not be candidates for chemotherapy. To identify potential candidates for the newly emerging immunotherapy-based treatment paradigms, we explored the clinical and biologic factors affecting treatment decisions. MethodsWe retrospectively reviewed the records of patients diagnosed at our university-affiliated cancer centre between 1 January 2011 and 31 December 2013. Patient demographics, syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…In our study, as patient comorbidity score increased, the likelihood of receiving treatment decreased. This is consistent with other studies that showed that patients with higher comorbidity burden are less likely to receive systemic treatment (20,52,53).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, as patient comorbidity score increased, the likelihood of receiving treatment decreased. This is consistent with other studies that showed that patients with higher comorbidity burden are less likely to receive systemic treatment (20,52,53).…”
Section: Discussionsupporting
confidence: 93%
“…Comparably, earlier studies have reported that up to 32% of patients with metastatic non-small-cell lung cancer could not receive treatment because of rapidly deteriorating ps 24 and had hypothesized that efficient work-up could lead to increased uptake of treatment 25 .…”
Section: Discussionmentioning
confidence: 71%
“…It is proposed as the most established factor for assessing prognosis and is advised in guidelines for lung cancer treatment [ 64 , 65 ]. Indeed, the Performance status represents a major criteria for treatment decision in advanced lung cancer as patients with a poor Performance status are expected to be unfit for conventional treatments [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%